A Pedagogias hospitalar e suas contribuições no proceso de desenvolvimento escolar de Carol, por meio do projeto hoje em Goiânia - GO - Silva, Dolores Ribeiro da (Universidade Federal do Tocantins, 2021)
This Course Conclusion Paper aims to present the contributions of Pedagogy Hospital through the Today Project in Goiânia - Goiás. For this, we carried out a Case Study with a young woman who had been supported by Hospital Pedagogy during her childhood, during intensive care and for the entire period she was ill, being thus considered as a student-patient. The methodology used for this study is called Case Study - Exploratory - Descriptive, under the theoretical direction of YIN (2015) and GODOY (1995). For the bibliographic research that deals with the study of Hospital Pedagogy, we chose as sources: Esteves (2008), Fontes (2006), Fonseca (1999) and Oliveira (2013), Lopes (2010). In view of the referential result, it was discovered that the first hospital class was inaugurated in Rio de Janeiro on August 14 (1950), at Hospital Municipal Jesus and since then the hospital classes in Brazilian states have grown considerably. The recognition took place when in 1995, it was adopted by Brazilian legislation and approved by the Brazilian Society of Pediatrics. In Goiânia it started in 1999 and this schooling process took place through the hospital classes maintained by NAEH (former Project Today), which started with the public policies of PEEDI - GO, which consolidated Pedagogy Hospital within the Goias state. To develop this proposal, we conducted an interview with the young woman who agreed to participate in the research. We prepared a script with 15 open-ended questions and the interview was conducted via the Zoom application, since the pandemic generated by the new corona virus - COVID-19 forced us to maintain social distance. The results of this research point out the challenges faced by the young woman in the teaching-learning process during the time she received the educational assistance from the Today Project. Thus, we hope that in the future this undergraduate thesis will allow a reflection on Hospital Pedagogy, and we believe that it will bring theoretical knowledge on the subject to future university students and / or pedagogues.